DIFUSI INOVASI DALAM KOMUNIKASI PEMASARAN POLITIK INDONESIA - I DEWA AYU HENDRAWATHY PUTRI (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2013)
Political world today can not be separated from the world of communications. Because the political activities based on communication in conveying ideas, ideas, opinions, and other matters relating to the state. According to Almond (1960), political communication is part of the seven political system that does not run itself, because communication helps other political systems. Opening market opportunities for products that politics is the result of conditioning by the mass media through information products. Information that shaped the values, image (image), and needs. The purpose of marketing communications is to reach a political understanding with or what's called mutual understanding between two or more participants to the communication of a message (in this case is a new idea) through certain communication channels. Thus the adoption of a new idea (innovation in politics) is influenced by participants' communication and communication channels. Communication channels can be said to play an important role in the spread of innovation, because it is through innovation that can spread to members of the social system. As in any other marketing activity, the existing political marketing